Molecular construction of Clostridium botulinum type A toxins. - Sugii, S (1975)
Two Clostridium botulinum type A toxic fractions, named large (L) and medium (M) toxins, were eluted from Sephadex G-200. Sucrose density gradient centrifugation resolved L toxin (2.5 X 10(8) to 3.0 X 10(8) mean lethal doses per mg of N) into two fractions, 19S and 16S. The same procedure performed at pH 8resolved it into three fractions; the heavier two were both nontoxic and hemagglutinin positive, and the lightest on (7S) was toxic. M toxin (12S) (4.5 X 10(8) to 5.0 X 10(8) mean lethal doses per mg of N) was homogeneous in electrophoresis and centrifugation at pH 6. The latter procedure performed at pH 8 dmonstrated that it dissociated into uniform 7S components. The nontoxic component of M toxin was free from hemagglutinin. M toxin alone was demonstrated in culture by sucrose density gradient centrifugation at pH 6. Dialysis of the culture supernatant resulted in partial formation of 16S toxin. Centrifugation of the crystalline toxin in 1 MNaCl demonstrated 16S toxin only. The toxic components of L, M, and crystalline toxins were antigenically identical. The nontoxic components of the crystalline and L toxins, consisting of two distinct antigens, were antigenically identical; that of M toxin was identical with one of these two antigens.